Who is using the UMLS and how - insights from the UMLS user annual reports - Fung, Kin Wah; Hole, William T; Srinivasan, Suresh (AMIA ... Annual Symposium proceedings, 2006)
The NLM's UMLS resources are available to users free of charge under a license that requires submission of an annual report on their usage. A new web-based template was used to collect users' annual reports for the calendar year 2004. Out of 2,677 li-censees, 1,427 (53%) submitted their annual reports through the web template. This represented a five-fold increase in the reports submitted compared to previous years. The information collected via the web template was more structured, more complete and easier to analyze. The main results from the 2004 annual reports are summarized and discussed. They are being used to guide UMLS developments.